Exploring Reading Comprehension Strategies: Insights from Recent Studies - Baiq Nadia Tiara Rizki, Baiq Nadia Tiara Rizki (Lembaga Bale Literasi, 2024)
This article provides an in-depth exploration of strategies for enhancing reading comprehension among students. The research examines innovative and traditional methods applied in varied educational contexts, highlighting approaches like Question-Answer Relationship (QAR), game-based learning, and cooperative techniques. Synthesizing findings from prior studies, the article underscores the pivotal role of emotional factors such as reading anxiety, motivation, and their interplay with comprehension. Moreover, the analysis considers the impact of technological advancements and the integration of flipped classrooms in fostering inferential and critical reading skills. Key findings reveal the importance of tailored interventions, equitable access to resources, and the incorporation of cohesion-focused instruction to address diverse learning needs. The paper concludes with practical recommendations for educators and a call for longitudinal studies to assess the sustainability and adaptability of these strategies in global contexts.